2010
DOI: 10.1021/ef901543m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cetane Number (CN) Improver on Combustion and Emission Characteristics of a Compression-Ignition (CI) Engine Fueled with an Ethanol−Diesel Blend

Abstract: Ethanol-diesel blended fuel has the potential to reduce diesel engine exhaust smoke and particulate emission as well as partially solve the energy crisis. However, with the increase of the ethanol fraction of the blends, the engine combustion will be affected significantly because of the change of fuel properties, especially the ignition delay (τ ig ). Generally, a cetane number (CN) improver should be added to improve the engine combustion. In this study, E30 (30 vol % of ethanol in the blend) was prepared. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Further, the lower cetane number of ethanol and methanol affects the auto ignition and hence to improve the ignition characteristics of the alcohol-diesel blends, researchers conceived strategies to modify the blend properties. In such measures, researchers contemplated on adding cetane improvers such as ethyl hexyl nitrate, peroxides and diethyl ether to the optimum blend and investigated the combustion characteristics such as ignition delay, peak heat release rate, combustion duration and pressure rise rate [44,[164][165][166][167][168]. From these studies, it has been unanimously reported that adding cetane number improver has a profound impact on improving the ignition characteristics of the blend.…”
Section: Blend Mode Operation Of Alcohol Based Fuelsmentioning
confidence: 99%
“…Further, the lower cetane number of ethanol and methanol affects the auto ignition and hence to improve the ignition characteristics of the alcohol-diesel blends, researchers conceived strategies to modify the blend properties. In such measures, researchers contemplated on adding cetane improvers such as ethyl hexyl nitrate, peroxides and diethyl ether to the optimum blend and investigated the combustion characteristics such as ignition delay, peak heat release rate, combustion duration and pressure rise rate [44,[164][165][166][167][168]. From these studies, it has been unanimously reported that adding cetane number improver has a profound impact on improving the ignition characteristics of the blend.…”
Section: Blend Mode Operation Of Alcohol Based Fuelsmentioning
confidence: 99%
“…The application of higher temperatures in RBO fuel has a great impact on the reduction of hydrocarbon condensation, hence leading to a decrease in emissions of HC [82,83]. An elevation in the cetane rating of RBO results in a decline in HC emissions as a consequence of a reduction in the duration of ignition delay [79,84,85]. The RBO00 variant demonstrates a maximum value of around 499 ppm under full load conditions.…”
Section: Carbon Dioxide (Co2)mentioning
confidence: 99%
“…It has been widely used as a major fuel, mainly in Brazil, or as a gasoline additive for octane improver and better combustion in the U.S.A. and Canada . Ethanol has also been used as an oxygen additive in diesel fuel to depress the soot and NO x emissions. One of the developed ethanol injection methods is called the diesel/ethanol compound combustion (DECC) system. In a DECC system, the engine will first operate on diesel alone to ensure cold-starting reliability and to avoid excessive aldehyde production at starting and low speed.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment setup: (1) high-pressure gas cylinders, (2) voltage regulator, (3) fuel tank, (4) motor speed control device,(5) injector, (6) pressure sensor, (7) injection valve, (8) quartz windows, (9) pressure sensor, (10) constant-volume bomb, (11) heater,(12) fuel pump, (13) electric motor,(14) signal triggers, (15) electromagnet,(16) controller, (17) high-speed camera, (18) SBC,(19) printer,(20) computer,(21) high-speed data acquisition devices, and (22 and 23) amplifiers.…”
mentioning
confidence: 99%